Foundations of a Sociology of Canon Law - Hahn, Judith (Springer eBook Collection, 2022)
Introduction: Why Write a Sociology of Canon Law? -- Canon Law Studies—A Theological Discipline -- Employing Juridical Methodology -- Employing Sociological Methodology -- How to Approach a Sociology of Canon Law -- The Sociological View of the Law -- The Law through a Sociological Lens -- A Sociological Focus on Canon Law -- The Functions of the Law -- Law and the Order of the Social -- Law and the Resolution of Conflicts -- The Validity of Positive Law -- Modern Law as Positive Law -- Law Derived from Power, Power Derived from the Law -- Characteristics of Positive Law -- The Validity of the Law and the Issue of Legitimacy -- A Sociological View on Validity Issues -- Accepting Canon Law? -- The Effectiveness of the Law -- Effectiveness and Compliance -- Preconditions of Compliance -- The Connection of the Effectiveness and Validity of the Law -- Résumé -- An Outlook for Further Studies -- Summary of the Book (in Theses).